2019
DOI: 10.1002/smtd.201900187
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Polyoxometalate into 3D Porous Li‐Containing Oxide: A Case Study of γ‐LiV2O5 for High‐Performance Cathodes of Li‐Ion Batteries

Abstract: The development of cathode materials with high Li storage capacity and fast Li‐ion diffusion kinetics is considered to be a promising way to extend the energy and power densities of Li‐ion batteries (LIBs). As potential high‐capacity cathode materials for LIBs, polyoxometalates (POMs) suffer greatly from inherent drawbacks. Therefore, another possibility for the application of POMs in LIBs is shown, which is to transform POMs into relevant 3D porous Li‐containing oxides. Here, a unique 3D porous γ‐LiV2O5 film … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 43 publications
1
29
0
Order By: Relevance
“…Hence, the crystal or surface structure of solid catalysts should be varied to not only enable the nucleation‐preferred formation of discharge products but also make the interaction between discharge products and catalyst surface appropriate. We believe that these rationales based on the growth dynamics of products from ORR/OER can be valid for a lot of solid catalysts and energy materials for future battery systems ranging from metals to oxides or hybrid materials …”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Hence, the crystal or surface structure of solid catalysts should be varied to not only enable the nucleation‐preferred formation of discharge products but also make the interaction between discharge products and catalyst surface appropriate. We believe that these rationales based on the growth dynamics of products from ORR/OER can be valid for a lot of solid catalysts and energy materials for future battery systems ranging from metals to oxides or hybrid materials …”
Section: Resultsmentioning
confidence: 91%
“…We believe that these rationales based on the growth dynamics of products from ORR/OER can be valid for a lot of solid catalysts and energy materials for future battery systems ranging from metals to oxides or hybrid materials. [39,40]…”
Section: Resultsmentioning
confidence: 99%
“…Vanadate‐based materials include alkaline metal vanadates and transition metal vanadates have been widely studied as electrodes for rechargeable batteries for more than 30 years, especially in regard to Li ion, [121–124] Na ion, [125–128] and Zn ion storage [108, 109] …”
Section: Cathode Materialsmentioning
confidence: 99%
“…Vanadate-based materials include alkaline metal vanadates and transition metal vanadates have been widely studied as electrodes for rechargeable batteries for more than 30 years, especially in regard to Li ion, [121][122][123][124] Na ion, [125][126][127][128] and Zn ion storage. [108,109] Mai's group reported novel Na 2 V 6 O 16 •1.63 H 2 O( H-NVO) nanowires, which possessed an excellent Zn 2 + storage capability and highly reversible property ( Figure 12).…”
Section: Metal Vanadatesmentioning
confidence: 99%
“…Many transition metal catalysts have been used as catalysts for epoxidation [5,6]. Catalyst precursors of polyoxometalate or polyoxometalate species catalyzed, H 2 O 2 -based epoxidation of alkenes with high selectivity to the epoxide and high efficiency of H 2 O 2 utilization is recently possible [7][8][9][10][11][12][13]. Zuwei Xi and Shuang Gao et al reported the reaction-controlled phase-transfer catalyst system based on polyoxometalate [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%